2006
DOI: 10.2139/ssrn.894063
|View full text |Cite
|
Sign up to set email alerts
|

International Migration with Heterogeneous Agents: Theory and Evidence

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 40 publications
(45 reference statements)
0
27
1
Order By: Relevance
“…However, differently from almost all existing literature, notable exceptions are Hatton (1995), Brücker and Schröder (2007) and Fachin (2007), we deeply investigate the dynamic characteristics of the series and study migration inside a cointegration framework.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, differently from almost all existing literature, notable exceptions are Hatton (1995), Brücker and Schröder (2007) and Fachin (2007), we deeply investigate the dynamic characteristics of the series and study migration inside a cointegration framework.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the burgeoning of both theoretical and empirical literature on migration in the recent years, it is surprising that very few works have dealt with the issues of non-stationarity and cointegration. Notable exceptions are Brücker and Schröder (2007) and the aforementioned works of Hatton (1995) and Fachin (2007). According to Hatton (1995) there exists a long-run relationship between the migration rate and the explanatory variables of equation (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus estimate determinants of migrants' stocks and not flows. Brücker and Schröder (2006) showed that empirical migration models estimating net migration flows instead of stocks may be misspecified: at the equilibrium, a positive relation exists between the stock of migrants while the net migration flow becomes zero. This is consistent with stylized facts that show that net migration rates tend to cease over time.…”
Section: Empirical Specification and Datamentioning
confidence: 99%
“…If regularization programs are implemented between the two censuses, the stocks of migrants in the second census and hence the size of the migration flows will increase in the data without actual movement of people. Another theoretical argument developed by Brücker (2006) suggests that using net migration flows instead of stocks might be misleading in the case of heterogeneous agents. This is especially important when it comes to estimating the impact of wage differentials on migration.…”
Section: Stocks Vs Flowsmentioning
confidence: 99%